Demand Analysis and Training Mode Research of E-commerce Talents in Guangxi Cross Border E-commerce Comprehensive Experimental Zone - Feng, Yongqiang; Koompai, Somjintana (Science, Technology, and Social Sciences Procedia, 2022)
In the context of the global epidemic, the rapid development of cross-border e-commerce has not only changed the operation mode of traditional e-commerce enterprises, established an ecosystem of coordinated development of e-commerce and international trade, and promoted the rapid development of cross-border e-commerce. However, the supply of talents for corresponding posts is far less than the demand. The cultivation of e-commerce professionals in higher vocational colleges faces new challenges. Starting from the research and analysis of the demand and training status of e-commerce talents in Guangxi cross-border e-commerce comprehensive pilot zone, the research objective of this paper is to study the relationship between post ability and professional skills, and the relationship between post ability and professional quality. The research method is to distribute network questionnaires to government departments, institutions and enterprises in Nanning city and Chongzuo City, Guangxi cross-border e-commerce comprehensive pilot zone, and collect 391 effective questionnaires; take professional skills and professional quality as independent variables and post capacity as dependent variables, and use statistical methods such as linear analysis to analyze the data to understand the demand of enterprises in Nanning cross-border e-commerce Comprehensive Experimental Zone and Chongzuo cross-border e-commerce comprehensive experimental zone for cross-border e-commerce talents. Based on this, analyze and summarize the talent types and typical job tasks required by enterprises, Then, the paper studies the training path of e-commerce professionals in Guangxi cross-border e-commerce comprehensive experimental zone. Through data analysis, the research result is that professional skills, professional quality and cross-border e-commerce post capacity are positively correlated. On this basis, this paper puts forward future research suggestions to improve the training mode of e-commerce talents in Guangxi cross-border e-commerce comprehensive experimental zone, and provides reference for the training of cross-border e-commerce talents and mode reform in Guangxi Higher Vocational Colleges.